ADDRESSING PRODUCTIVE AGING NEEDS OF AT-RISK OLDER ADULTS THROUGH THE SENIOR COMMUNITY SERVICES EMPLOYMENT PROGRAM. (11th November 2018) - Yulikova, O; Yu, P
Abstract: SCSEP is a unique program among the federal workforce programs in preparing older workers to return to the workforce. SCSEP participants are chronically unemployed, with 27+ weeks of unemployment. One of the long-term barriers to employment, among them maybe ageism. When older workers are given a chance, many employers recognize their value. SCSEP helps improve employment outcomes by providing an on-the-job training opportunity to the participants. 160 nationwide employers satisfaction survey was administered by the SCSEP grantees from February 1, 2016, to March 15, 2017. The American Customer Satisfaction Index (ACSI) was used. The average cross-industry ACSI score is 77.0. Nationwide SCSEP ACSI scores for nationwide employer satisfaction score was 85.5. The high value of SCSEP focus on older workers for the employers will be demonstrated and discussed. Also, the larger implications of the SCSEP model on the implementation of the Workforce Innovation and Opportunity Act, 2014 will be demonstrated.